Business Plan: WindScanner.PT - Grosso, José (2022)
ABSTRACT: Wind energy is becoming one of the leading sources of power in Europe. The installed capacity increases each year, with the offshore wind gradually evolving with even more significant potential than onshore. This growing tendency has also been promoting a more extensive research effort in this area, pushed by the climatic crisis that has also driven political support from multiple nations across Europe. Wind energy has employed over 250 thousand EU citizens and contributed to around 10% of European electrical consumption. Although high milestones have been achieved, there is still much room to grow in the wind energy sector, particularly cost reduction. The WindScanner.pt project aims to create a European distributed research infrastructure based on high precision sensors able to analyze fluid dynamics in tridimensional volumes, offering the ability to understand atmospheric conditions and turbulence better. This asset will not only allow better assessment of the wind conditions. Still, it will also enable the evaluation of projects in other areas where fluid dynamics are relevant, such as civil engineering and the building industry, by scanning the surroundings of large structures such as bridges and viaducts and measuring structure oscillations.